Comprehensive Cardiac Rehabilitation for Secondary Prevention After Transient Ischemic Attack or Mild Stroke: PSYCHOLOGICAL PROFILE AND OUTCOMES. Issue 6 (November 2017) - Prior, Peter L.; Hachinski, Vladimir; Chan, Richard; Unsworth, Karen; Mytka, Sharon; Harnadek, Michael; O'Callaghan, Christina; Suskin, Neville
Abstract : Purpose: Having previously reported that comprehensive cardiac rehabilitation (CCR) is effective for secondary prevention post-transient ischemic attack (TIA)/mild nondisabling stroke (MNDS), we present psychometric findings for the same sample that elucidate subacute TIA/MNDS psychological outcomes and test whether CCR would be independently associated with psychological improvements. Methods: In this prospective cohort trial patients with ≥1 risk factor, recruited from a stroke prevention clinic within 12 months (mean = 11.5 weeks) post-TIA/MNDS, entered CCR. Results: Of the 110 recruited patients, 100 (mean age = 65.4 years; 46 females) entered CCR and 80 completed CCR (mean duration = 7.6 months). At CCR entry, 16.5% and 39.2% screened positively for depression and anxiety, decreasing nonsignificantly at exit to 4.2%, and significantly to 16.9% ( P = .008), respectively. Age-corrected deficits occurred more frequently than expected ( P ⩽ .03); at entry, mental health status (13.3%), clock-drawing (31.6%), oral-verbal fluency (16.9%), word-list learning (11.2%), and recall (12.6%); at exit, clock-drawing (30.0%). Entry-to-exit, mean depression, anxiety, mental and physical health status, word-list learning, memory, digit-symbol coding, and oral-verbal fluency scores improved significantly ( P ⩽ .031). No reliable change indices were significant. Psychological service recipients improved significantly more than nonrecipients in depression ( P = .049). Baseline North American Adult Reading Test score predicted exercise attendance ( R = 0.275; P = .044); New York Heart Association (NYHA) class and depression score predicted exit physical health status ( R = 0.770, P < .001); and depression score predicted exit mental health status ( R = 0.523, P < .001). Conclusions: Anxiety and executive dysfunction persisted post-TIA/MNDS. Although promising for secondary prevention post-TIA/MNDS, CCR was not independently associated with psychological improvements. CCR psychological treatment may benefit depression. Subacute NYHA class and depression may later affect quality of life. Abstract : We report on psychological outcomes from patients with TIA/mild stroke in comprehensive cardiac rehabilitation. TIA/mild stroke were associated with transient depression responsive to psychological intervention; mental health status, verbal learning, and memory deficits; and persistent anxiety and executive dysfunction. Although promising for post-TIA/mild secondary prevention, comprehensive cardiac rehabilitation was not independently associated with observed psychological improvements.